Conceptual analysis of value-based management and accounting: with reference to Japanese practices / Akira Nishimura - Nishimura, Akira (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2007)
The aim of this paper is to outline and discuss the framework of contemporary management accounting known as ‘value-based management accounting’. At present, under the severe competition in the international markets, short-lived consumer sentiment and rapid change in technology, management should enhance not only the effective and efficient value of product but also enterprise value for competitive advantage. This value management should look so forward and be so proactive as to be not swung around risk and uncertainty, while management accounting should also serve the management as a supplier of useful information on risk and opportunity.